2010
DOI: 10.1124/jpet.110.170191
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Phosphodiesterase-5 Inhibitor Tadalafil Attenuates Doxorubicin-Induced Cardiomyopathy without Interfering with Chemotherapeutic Effect

Abstract: Doxorubicin (DOX) is one of the most effective anticancer drugs. However, its cardiotoxicity remains a clinical concern that severely restricts its therapeutic usage. We designed this study to investigate whether tadalafil, a long-acting phosphodiesterase-5 (PDE-5) inhibitor, protects against DOX-induced cardiotoxicity. We also sought to delineate the cellular and molecular mechanisms underlying tadalafil-induced cardioprotection. Male CF-1 outbred mice were randomized into three groups (n ϭ 15-24/group) to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 38 publications
(35 reference statements)
6
66
0
3
Order By: Relevance
“…Additionally, the antiapoptotic protein Bcl-2 was significantly declined after treatment in the DOX group compared with the sildenafil + DOX and control groups, suggesting a pivotal role of Bcl-2 in altering the pathological process leading to end-stage heart failure. More recently, we showed that tadalafil, the long acting PDE-5 inhibitor, also improved LV function by preserving fractional shortening (LVFS) and ejection fraction (LVEF) compared with DOX-treated mice (Figure 2) (Koka et al, 2010). This study also demonstrated that tadalafil improved survival rates in mice without interfering with the anti-tumor effect of DOX.…”
Section: Pde-5 Inhibitors Protect Against Dox-induced Cardiomyopathysupporting
confidence: 51%
“…Additionally, the antiapoptotic protein Bcl-2 was significantly declined after treatment in the DOX group compared with the sildenafil + DOX and control groups, suggesting a pivotal role of Bcl-2 in altering the pathological process leading to end-stage heart failure. More recently, we showed that tadalafil, the long acting PDE-5 inhibitor, also improved LV function by preserving fractional shortening (LVFS) and ejection fraction (LVEF) compared with DOX-treated mice (Figure 2) (Koka et al, 2010). This study also demonstrated that tadalafil improved survival rates in mice without interfering with the anti-tumor effect of DOX.…”
Section: Pde-5 Inhibitors Protect Against Dox-induced Cardiomyopathysupporting
confidence: 51%
“…Hücrede cGMP (siklik guanozin monofosfat) yıkımını engelleyen ve stoplazmik cGMP konsantrasyonunu arttırarak etkisini göste-ren bu grup ilaçların anti-oksidan etkilerini gösteren çalışmalar da vardır (14)(15)(16)(17)(18)(19)(20)(21)(22). Farklı dozlarda ve farklı sürelerde uygulanan PDE5 inhibitörlerinin; diyabet (14,15), iskemi-reperfüzyon (16)(17)(18), pulmoner hipertansiyon (19,20) ve kardiyomiyopati (21) gibi deneysel modellerde kalp, böbrek, over ve kavernöz dokularda oksidatif stresi azaltıp fonksiyonel iyileşme sağladığı gösterilmiştir.…”
Section: Introductionunclassified
“…A number of pioneering investigations from our laboratory have demonstrated that PDE-5 inhibitors attenuate doxorubicin-induced cardiomyopathy in animal and cell models (Koka et al, 2010;Das et al, 2010). In a recent study, we tested whether sildenafil potentiates the antitumor efficacy of doxorubicin in prostate cancer.…”
Section: Pde-5 Inhibitors Protect Against Doxorubicin-induced Cardiacmentioning
confidence: 99%
“…In a separate study, tadalafil improved left ventricular function and prevented cardiomyocyte apoptosis in doxorubicin-induced cardiomyopathy through mechanisms involving upregulation of cGMP, PKG activity, and MnSOD level without interfering with the chemotherapeutic benefits of doxorubicin (Koka et al, 2010). In these studies, adult male CF-1 mice were randomized to receive saline (0.2 ml i.p.…”
Section: Pde-5 Inhibitors Protect Against Doxorubicin-induced Cardiacmentioning
confidence: 99%